Manajemen Kompensasi Bagi Karyawan Industri Pengelola Venue Event Olahraga (Studi Kasus: PT. Jakabaring Sport City) - Muhammad Iqbal Djohan; Ahmad Kurniawan (Politeknik Pariwisata Makassar, 2023)
The difference in the management of compensation given to employees of PT Jakabaring Sport City as an industry for managing sport event venues in Palembang City is not in accordance with the rules issued by the Ministry of Manpower of the Republic of Indonesia. The only compensation given is salary, incentives and facilities. However, in theory (Henry Simamora, 2004) explains that compensation must be given in the form of four categories including salary, benefits, incentives, and facilities that support the work of the employee. Therefore, it is interesting for researchers to examine this research more comprehensively. The purpose of this study is to find out how the differences in management of compensation in the form of four types need to be carried out in accordance with the theory that supports this phenomenon. The research method used is descriptive quantitative method on saturated sampling or census, because the samples taken in this study were less than twenty respondents. Thus, the aims and objectives of this research can be clearly measured. From the research method that has been carried out, it provides results and discussion that salaries, benefits, incentives and facilities that have been given to employees so far are not in accordance with the rules and performance loyalty that they have given to the company.